Cardiac index and hepatopulmonary syndrome in liver transplantation candidates: The pulmonary vascular complications of liver disease study. Issue 5 (3rd May 2023) - DuBrock, Hilary M.; Forde, Kimberly; Krok, Karen; Patel, Mamta; Al-Naamani, Nadine; Lin, Grace; Oh, Jae K.; Fallon, Michael B.; Kawut, Steven M.; Krowka, Michael J.
Background and Aims: Hepatopulmonary syndrome (HPS) and a hyperdynamic circulation are common complications of advanced liver disease, but the relationship between HPS and cardiac index (CI) is poorly understood. We sought to compare CI in patients with and without HPS and to assess the relationship between CI and symptoms, quality of life, gas exchange, and exercise capacity among liver transplantation (LT) candidates. We performed a cross-sectional analysis within the Pulmonary Vascular Complications of Liver Disease 2 study, a multicenter prospective cohort study of patients being evaluated for LT. We excluded patients with obstructive or restrictive lung disease, intracardiac shunting, and portopulmonary hypertension. We included 214 patients (81 with HPS and 133 controls without HPS). Compared with controls, patients with HPS had a higher CI (least square mean 3.2 L/min/m 2, 95% CI 3.1–3.4 vs. 2.8 L/min/m 2, 95% CI 2.7–3.0, p < 0.001) after adjustment for age, sex, Model for End-stage Liver Disease-Sodium (MELD-Na) score and beta-blocker use, and a lower systemic vascular resistance. Among all LT candidates, CI was correlated with oxygenation (Alveolar-arterial oxygen gradient r =0.27, p < 0.001), intrapulmonary vasodilatation severity ( p < 0.001), and biomarkers of angiogenesis. Higher CI was independently associated with dyspnea and worse functional class and physical quality of life after adjusting for age, sex, MELD-Na, beta-blocker use, and HPS status. HPS was associated with a higher CI among LT candidates. Independent of HPS, higher CI was associated with increased dyspnea and worse functional class, quality of life, and arterial oxygenation.